Resilience of Caregivers in Caring for Families with Schizophrenia: A Case Study in Bogor - Saputro, Renata; Wicaksono, Ade Iva; Paramita, Anindya Dewi (Jurnal Psikologi Terapan, 2023)
This study aims to describe resilience in caregivers of families with members suffering from schizophrenia. Schizophrenia is a severe mental disorder that affects thought processes and behavior, requiring intensive support from families as caregivers. However, families often face significant burdens, including emotional, social, and economic challenges, which demand strategies and strength to overcome emerging crises. This research employed a qualitative method with a case study approach, involving three caregivers living with family members diagnosed with schizophrenia in Bogor. Data were collected through in-depth interviews and observations, then analyzed using thematic analysis. The results reveal that caregivers exhibit strong resilience in addressing various challenges. Strategies include religious approaches, such as drawing closer to God, receiving support from extended family, and adopting behavioral changes to enhance the quality of care. Additionally, they demonstrated optimism, effectively analyzed the root causes of issues, and leveraged social support as a resource for overcoming difficulties. The study concludes that resilience is a crucial factor in supporting the care process for individuals with schizophrenia and helps caregivers manage challenges more effectively. The implications of this research suggest the need for strengthening resilience factors through psychosocial interventions, community support, and family-based mental health services.